GAMBARAN DISIPLIN GURU PAUD DI KECAMATAN PEKANBARU KOTA, KOTA PEKANBARU - Okti Susita; Zulkifli N Zulkifli N; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This study aims to determine the description of Discipline Master ECD in Sub Pekanbaru City. As to be observed in this study is how is the discipline of early childhood teachers in the district of Pekanbaru City. Methods of data collection in this study using a questionnaire. The data analysis technique used in this study is a partial correlation techniques with the help of SPSS 16.0 for facilities windos. The results showed the level known that the reliability of the instrument overview discipline early childhood teachers in the district of Pekanbaru City, Pekanbaru is 0.940, with table r Product Moment obtained r table = 0.444 (for n = 24), then 0.940> 0.444, it means the instrument overview early childhood teachers in the district discipline Pekanbaru, Pekanbaru reliable. Discipline Teachers ECD in District 79.31% with the category very disciplined. The conclusion of this study is Discipline Master ECD in Sub Pekanbaru City has been very good.Keywords: Discipline, Teacher